2017
DOI: 10.1111/febs.14122
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell death and mitochondrial fission by ERK1/2 MAP kinase signalling

Abstract: The ERK1/2 signalling pathway is best known for its role in connecting activated growth factor receptors to changes in gene expression due to activated ERK1/2 entering the nucleus and phosphorylating transcription factors. However, active ERK1/2 also translocate to a variety of other organelles including the endoplasmic reticulum, endosomes, golgi and mitochondria to access specific substrates and influence cell physiology. In this article, we review two aspects of ERK1/2 signalling at the mitochondria that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
124
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 134 publications
3
124
1
1
Order By: Relevance
“…The present study demonstrated that KRT17 knockdown decreased the level of ERK1/2 phosphorylation, suggesting that upregulation of KRT17 participated in EMT and migration in PAC tumorigenesis. In the majority of cancer types, ERK1/2 signaling promotes cell survival by inhibiting the function of pro-death proteins, including Bad (47). In the present study, Bad phosphorylation increased following KRT17 silencing using KRT17-shRNA lentivirus transfection.…”
Section: Discussionsupporting
confidence: 53%
“…The present study demonstrated that KRT17 knockdown decreased the level of ERK1/2 phosphorylation, suggesting that upregulation of KRT17 participated in EMT and migration in PAC tumorigenesis. In the majority of cancer types, ERK1/2 signaling promotes cell survival by inhibiting the function of pro-death proteins, including Bad (47). In the present study, Bad phosphorylation increased following KRT17 silencing using KRT17-shRNA lentivirus transfection.…”
Section: Discussionsupporting
confidence: 53%
“…[ 41,42 ] Similar to the dual functional role of p38 activation, the ERK1/2 activation cannot only promote cell proliferation but also drive cell senescence/apoptosis depending on dose, duration, cell type, and other factors. [ 43,44 ] However, it remains an ongoing research how the cells “decide” to respond to stimuli (e.g., butyrate treatment) by preferentially undergoing cell proliferation or cell cycle arrest/apoptosis. Our butyrate‐treatment data (Figure 6) suggest that an increase in activation of p38 and ERK1/2 may inhibit cell proliferation in HCT‐116 cells while a decrease in p38 activation may also decrease cell proliferation in DCA‐RCL cells.…”
Section: Discussionmentioning
confidence: 99%
“…13 The extracellular signal-regulated kinase 1/2 (ERK1/2) can be activated and/ or up-regulated by upstream kinases, transcription factors and/ or differentiation factor. [14][15][16] Activated ERK1/2 translocates to the cell nucleus and then phosphorylates a series of transcription factors, such as c-MYC, FOS, FRA1 and EGR1. [17][18][19][20][21][22][23] These ERK1/2-activated downstream factors further regulate many cellular functions, including proliferation, differentiation and transformation.…”
Section: Introductionmentioning
confidence: 99%